Indagini geofisiche per la mappatura dei fondali e delle antiche strutture portuali sommerse di Sinuessa - Alfredo Trocciola; Carmine Minopoli; Raffaele Pica; Pasquale Sarao (Archeomatica, 2014)
The geophysical surveys, in the marine environment of archaeological interest, quickly and accurately allow the reconstruction of significant areas of the seabed. The mapping of geomorphological and anthropogenic artifacts with these technologies is of particular importance in areas where the turbidity of the water makes it difficult to overview. In the campaign of investigations carried out by ENEA about the port facilities in Sinuessa, it was decided to employ a high-resolution side scan sonar (400-900 MHz). The investigations allowed to have a brand new image of the seabed as well as the location of the remains of the ancient maritime works with DGPS technology.